2023
DOI: 10.1021/acsnano.2c10701
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the Asymmetric Atomic Interface of Copper Single Atoms for Efficient CO2 Electroreduction

Abstract: Cu single-atom catalysts (Cu SACs) have been considered as promising catalysts for efficient electrocatalytic CO 2 reduction reactions (ECRRs). However, the reports on Cu SACs with an asymmetric atomic interface to obtain CO are few. Herein, we rationally designed two Cu SACs with different asymmetric atomic interfaces to explore their catalytic performance. The catalyst of CuN 3 O/C delivers high ECRR selectivity with an FE CO value of above 90% in a wide potential window from −0.5 to −0.9 V vs RHE (in partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…93 For example, Cu−N 2 sites with unsaturated coordination environment exhibited short bond length, which could accelerate the transfer of electrons from active sites to CO 2 *. 94 And Song et al 95 reported an adjusting strategy of asymmetric atomic interface (Cu−O/C and Cu−O/ N coordination) of Cu SACs (Figure 7a). The rate-determining step (CO desorption) occurred more easily at CuN 3 O sites than at CuCO 3 sites, resulting in CuN 3 O sites exhibiting a large turnover frequency (TOF) up to 2782.6 h −1 and higher selectivity (Figure 7b).…”
Section: Ad Cu Catalysts For C 1 Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…93 For example, Cu−N 2 sites with unsaturated coordination environment exhibited short bond length, which could accelerate the transfer of electrons from active sites to CO 2 *. 94 And Song et al 95 reported an adjusting strategy of asymmetric atomic interface (Cu−O/C and Cu−O/ N coordination) of Cu SACs (Figure 7a). The rate-determining step (CO desorption) occurred more easily at CuN 3 O sites than at CuCO 3 sites, resulting in CuN 3 O sites exhibiting a large turnover frequency (TOF) up to 2782.6 h −1 and higher selectivity (Figure 7b).…”
Section: Ad Cu Catalysts For C 1 Productsmentioning
confidence: 99%
“…(b) TOF values of CuNO 3 /C and CuCO 3 /C for CO production based on the loading amount of Cu atoms at different applied potentials. Reprinted with permission from ref . Copyright 2023 American Chemical Society.…”
Section: Ad Cu Catalysts For C1 Productsmentioning
confidence: 99%
“…The DG values of different steps of OH*, O*, and OOH* were selected to elucidate the electrocatalytic activity mechanism. 39,40 The theoretical initial potentials for the OER on CoS, MoCoS and VCoS were calculated using eqn (S1) (ESI †). The rate-determining step (RDS) is the step with the largest DG n value for the fourelectron process.…”
Section: Electrocatalytic Enhancement Mechanismmentioning
confidence: 99%
“…In addition, the CuN 3 O/ C reported by Song et al demonstrated good performance at −0.8 V with a FEco of 96%. 52 Researcher Cong Liu reported the preparation of single-atom carbon-loaded Cu catalysts using a Cu-Li hybrid approach (Fig. 5e).…”
Section: Supported Cu Single-atom Catalystsmentioning
confidence: 99%
“…In addition, the CuN 3 O/C reported by Song et al demonstrated good performance at −0.8 V with a FEco of 96%. 52…”
Section: Supported Cu-based Catalysts For the Co2rrmentioning
confidence: 99%